Cultural Lexicon of the Tayuban Tradition in Ngoreyan Hamlet, Ngandong Village, Gantiwarno District, Klaten Regency, Boxing: Ethnolinguistic Studies - Dwi Larasati; Hendrokumoro Hendrokumoro (International Journal Labs, 2025)
This research aims to identify and describe the cultural lexicon and cultural meaning contained in the tayuban tradition that takes place in Ngoreyan Hamlet, Ngandong Village, Gantiwarno District, Klaten Regency. This study uses a descriptive method with a qualitative approach. The data in this study is in the form of vocabulary related to the elements of the tayuban tradition, including equipment, actors, and procedures or implementation processes. Data was obtained through observation, interview, recording, and recording techniques of informants who were directly involved in the implementation of the tradition. Furthermore, the data were analyzed using an interactive qualitative analysis model from Miles and Huberman. The results of this study show that there is a distinctive cultural lexicon in the tayuban tradition that reflects the names of equipment, actors, and procedures for its implementation, which contain cultural values and local wisdom of the local community.